Cooperative Learning Berbantuan Media Teka-Teki Silang Edukasi untuk Meningkatkan Kerjasama dan Prestasi Belajar PKn - Kristiana Wiji Rahayu (Universitas Muhammadiyah Magelang, 2020)
This study aims to improve collaboration and student learning achievement PKn through the application of cooperative learning models assisted by educational crossword puzzles. This Classroom Action Research was conducted at SMP Negeri 5 Banjarnegara class IX E in semester 2 of 2018/2019 Academic Year. The study was conducted in 2 cycles. The data in this study were obtained through observation and written test methods. The results showed that the ability of students to collaborate had increased from pre cycle (27.38%), cycle 1 (72.13%) and cycle II (88%). The average value of PKn student learning achievement also increased from pre-cycle (76.27), cycle I (81.46) and cycle II (87.62). While students' learning completeness experienced a significant increase, from pre-cycle (53.85%), cycle I (80.77%) and cycle II (100%). So it can be concluded that the application of the Cooperative Learning Model Aided by Educational Crossword Puzzles can improve students' PKn collaboration and learning achievement.